(untitled) (Thobaqot: Jurnal Ilmu Hadis, 2023)
Bullying is an aggressive act that hurts someone and makes that person suffer. The aim of this research was to determine the quality and authenticity of the sanad and matan hadith, to understand the meaning of hadith regarding responding to bullying behavior, and to find out the impact and solutions to bullying behavior. This research uses a type of qualitative method sourced from literature (library research) and data collection was obtained by research from the Musnad Ahmad bin Hanbal book and assisted by other hadith books. Then the results of the research can be analyzed using the takhrij, i’tibar, critic sanad, and matan methods. The results of the research in Ahmad bin Hanbal’s musnad book are of authentic quality. Meanwhile, in matan the quality of hadith is authentic because it does not conflict with the Koran, similar hadiths, or more authentic hadiths. Thus this hadith can be used as evidence. Based on several studies, the factors that cause bullying behavior include family factors, school factors, peer factors, and mass media factors. These factors can cause several impacts that occur from bullying behavior, victims of bullying, and those involved in this behavior, such as depression, isolation, and so on. In the Qur’an, several solutions are explained for someone who is depressed to restore self-confidence in the victim or perpetrator of bullying.